Water extraction of bioactive compounds from plants to drug development - Domínguez González, Herminia; Muñoz González, María Jesús (Amsterdam Elsevier, 2018)
Water Extraction of Bioactive Compounds: From Plants to Drug Development draws together the expert knowledge of researchers from around the world to outline the essential knowledge and techniques required to successfully extract bioactive compounds for further study. The book is a practical tool for medicinal chemists, biochemists, pharmaceutical scientists and academics working in the discovery and development of drugs from natural sources. The discovery and extraction of bioactive plant compounds from natural sources is of growing interest to drug developers, adding greater fuel to a simultaneous search for efficient, green technologies to support this. Particularly promising are aqueous based methods, as water is a cheap, safe and abundant solvent. Water Extraction of Bioactive Compounds: From Plants to Drug Development is a detailed guide to the fundamental concepts and considerations needed to successfully undertake such processes, supported by application examples and highlighting the most influential variables. Beginning with an introduction to plants as sources of drugs, the book highlights the need for a move towards both more rational and greener techniques in the field, and presents multiple innovative water-based strategies for the discovery and extraction of bioactive constituents of botanicals. A broad range of available techniques are reviewed, including conventional and pressurized hot water extraction techniques, intensified processes such as microwave-assisted, ultrasound-assisted processes, and enzyme assisted extraction, and processes using combined techniques.--Provided by publisher.
Chapter 1 - Introduction -- Chapter 2 - Therapeutic Compounds From Plants Using Subcritical Water Technology -- Chapter 3 - Hydrolysis of Biopolymers in Near-Critical and Subcritical Water -- Chapter 4 - Subcritical Water Extraction and Neoformation of Antioxidants -- Chapter 5 - Extraction of Oligosaccharides With Prebiotic Properties From Agro-Industrial Wastes -- Chapter 6 - Microwave-Assisted Water Extraction -- Chapter 7 - Microwave-Assisted Water Extraction of Carbohydrates From Unutilized Biomass -- Chapter 8 - Microwave-Assisted Extraction of Flavonoids -- Chapter 9 - Microwave-Assisted Extraction of Betalains -- Chapter 10 - Microwave-Assisted Pressurized Hot Water Extraction of Alkaloids -- Chapter 11 - Fundamentals of Ultrasound-Assisted Extraction -- Chapter 12 - Ultrasound-Assisted Extraction of Bioactive Carbohydrates -- Chapter 13 - Enzyme-Assisted Aqueous Extraction Processes -- Chapter 14 - Enzyme-Assisted Extraction of Phenolic Compounds -- Chapter 15 - Silymarin Extraction From Silybum marianum L. Gaertner -- Chapter 16 - Potential of Novel Technologies for Aqueous Extraction of Plant Bioactives -- Chapter 17 - Combination of Water-Based Extraction Technologies -- Index.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Plant bioactive compounds -- Separation; Pharmaceutical technology; Electronic books